Fit for life : Looking Good ... Feeling Great : A Guide to a Healthier You - Ager, Anne D.; et al (Guildford Colour Library Books, 1986)
"Although it is true that good health is something that cannot be bought, every one of us can ensure that our bodies remain in as good a condition as nature will allow. Fit for Life is the all-in-one guide to maintaining the body at the very peak of physical perfection."
Include Color Illustration, Tables and Index
Keywords: Health -- Recipes -- Fitness